K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

13 tháng 2 2018

-12+3(-x+7)=-18

-12-3x+21=-18

9-3x=-18

3x=27

x=9

13 tháng 2 2018

- 12 + 3 ( - x + 7 ) = - 18

- 3x + 3 . 7 = -18 + 12

- 3x + 21 = - 6

- 3 x = - 6 - 21

- 3x = - 27

x = - 27 : ( - 3 )

x = 9

27 tháng 3 2017

a.1/4

b.-7/144

c.25/21

d.17/7

e.80/63

f.9/7

27 tháng 3 2017

a)1/4

b)-7/144

c)-25/21

d)17/7

e)16/63

f)9/7

25 tháng 3 2018

Tự làm đi, lười thế

25 tháng 3 2018

a) x= 1/4

b) x= -7/144

c) x= 25/6

d) x=17/7

e) x= 80/63

f) x= -45/14

4 tháng 2 2017

-12+3(-x+7)=-18

-9(-x+7)=-18

9x-63=-18

9x=-18+63=45

x=45:9=5

31 tháng 12 2021

-12 + 3 . (-x + 7) = -18

→ 3 × (-x + 7) = -18 - (-12)

→ 3 × (-x + 7) = -18 + 12

→ 3 × (-x + 7) = -6

→ -x + 7 = -6 : 3

→ -x + 7 = -2

→ -x = -2 - 7

→ -x = -9

→ x = 9

Vậy x = 9

17 tháng 1 2019

5.(x+7)=3.(2-x)

=>5x+35=6-3x

=>5x+3x=6+41

=>8x=47

=>x=47:8=47/8

17 tháng 1 2019

\(12\left(x-3\right)=5\left(x-1\right)+4\)

\(\Rightarrow12x-36=5x-5+4\)

\(\Rightarrow12x-5x=-5+4+36\)

\(\Rightarrow7x=35\)

\(\Rightarrow x=5\)

\(-6\left(x-7\right)+2\left(x+10\right)=x-18\)

\(-6x+42+2x+20=x-18\)

\(-6x+2x-x=-18-20-42\)

\(-5x=-80\)

\(x=16\)

\(7\left(2x-1\right)-12\left(x-5\right)=3\)

\(\Rightarrow14x-7-12x+60=3\)

\(\Rightarrow14x-12x=3-60+7\)

\(\Rightarrow2x=-50\)

\(\Rightarrow x=-25\)

17 tháng 1 2019

\(\left|2x-1\right|=17\)

\(\Leftrightarrow\orbr{\begin{cases}2x-1=17\\2x-1=-17\end{cases}}\)

\(\Leftrightarrow\orbr{\begin{cases}x=9\\x=-8\end{cases}}\)

\(\left|8-3x\right|=14\)

\(\Leftrightarrow\orbr{\begin{cases}8-3x=14\\8-3x=-14\end{cases}}\)

\(\Leftrightarrow\orbr{\begin{cases}x=-2\\x=\frac{22}{3}\end{cases}}\)

14 tháng 2 2020

1) -12+3.(-x+7)=-18

   3.(-x+7)=-18+12

   3.(x+7)=-6

x+7=-6:3

x+7=-2

x=-2-7

x=-9

14 tháng 2 2020

Trl :

   Bạn kia trả lời đúng rồi !

Hok tốt

~ nhé bạn ~

19 tháng 1 2017

-12 + 3(-x + 7 ) = -18 

        3(-x + 7 ) = (-18 ) - (-12)

        3(-x + 7 ) = -6

           -x + 7  = (-6) : 3

           - x + 7 = 2

                  -x = 2-7

                  -x = -5

              vậy x = 5

24 : ( 3x - 2 ) = -3

        3x - 2   = 24 : (-3)

        3x - 2   = -8

              3x  = -8 + 2 

              3x  = -6

               x   = (-6) : 3 

               x  = -2

          vậy x = -2

-45 : 5(-3 - 2x ) = 3

        5( -3 - 2x ) = (-45) : 3

        5( -3 - 2x ) = -15

            -3 - 2x   = (-15) : 5

            -3 - 2x   = (-3)

                  2x   = (-3) : (3)

                  2x   = 0

                   x    = 2 : 0

                   x    = 0

           vậy x     =   0